Babesia canis, ehrlichia canis e rangelia vitalii : aspectos clínicos, parasitológicos, hemato-sorológicos e moleculares de cães infectados da região de Passo Fundo-RS-Brasil - Gottlieb, Juliana (2014)
The purpose of this study was to diagnose the causative agents of infection in dogs with suspected hemoparasites treated during the clinical routine of the Veterinary Hospital at the University of Passo Fundo, in the municipality of Passo Fundo, RS, Brazil. Dogs with depression, anorexia and fever were screened for completion of a questionnaire and had venous blood samples analyzed by complete blood count, peripheral blood smear test, indirect immunofluorescence assay (IIFA) and polymerase chain reaction (PCR). Of 58 sampled dogs, 3 (5.2%) and 8 (13.8%) were seropositive in the IIFA for the antigens against E. canis and B. canis, respectively. In PCR, 4 (6.8%) dogs were positive for R. vitalii and 1 (1.7%) dog was positive for E. canis. No dogs were positive for B. canis in the molecular analysis. The PCR products were sequenced and the E. canis and R. vitalii DNAs were genetically similar (99%) to E. canis and R. vitalii strains isolated in Brazil. We emphasize the importance of the first molecular detection of E. canis in dogs in the state of Rio Grande do Sul, Brazil